Enhancing non-technical skills by a multidisciplinary engineering summer school. (2nd November 2017) - Larsen, Peter Gorm; Kristiansen, Erik Lasse; Bennedsen, Jens; Bjerge, Kim
ABSTRACT: In general engineering studies focus on the technical skills in their own discipline. However, in their subsequent industrial careers, a significant portion of their time needs to be devoted to non-technical skills. In addition, in an increasingly globalised world collaboration in teams across cultures and disciplines is paramount to the creation of new and innovative products. In order to enhance the non-technical skills for groups of engineering students a series of innovation courses has been arranged and delivered in close collaboration with an industrial company (Bang & Olufsen). These courses have been organised as summer schools called 'Conceptual Design and Development of Innovative Products' (CD-DIP) and delivered outside the usual educational environment. In order to explore the impact of this single course, we have conducted a study among the students participating from 2007 to 2013. This has been carried out both qualitatively using interviews with selected students as well as quantitatively using a survey. The results are outstanding in demonstrating that the non-technical skills obtained in this single course have been of high value for a large portion of the students' subsequent professional life.